Neuroscience for dummies : - Amthor, Frank (John Wiley &​ Sons, Inc, 2016)
Content: the brain. Covering the most recent scientific discoveries and complemented with helpful diagrams and engaging anecdotes that help bring the information to life, this updated edition offers a compelling and plain-English look at how the brain and nervous system function.